Professional iOS database application programming - Alessi, Patrick (Programmer to programmer., 2013)
Updated and revised coverage that includes the latest versions of iOS and Xcode Whether you're a novice or experienced developer, you will want to dive into this updated resource on database application programming for the iPhone and iPad. Packed with more than 50 percent new and revised material - including completely rebuilt code, screenshots, and full coverage of new features pertaining to database programming and enterprise integration in iOS 6 - this must-have book intends to continue the precedent set by the previous edition by helping thousands of developers master database.